Fe(II) Induced Oxidation of Formic Acid - Zaheer, Ahmed; Ahmed Farooqui, Mazahar; Mohammad Arif, Pathan (Asian Journal of Chemistry, 2010)
The mechanistic proposals of induced oxidation of formic acid (acceptor) by Fe(II) (inductor) were investigated. A volumetric method was used to calculate the induction factor (I.F). The oxidation is carried out in acidic media by using KMnO4 as an actor. The effects of salts were studied by keeping the sulphuric acid concentration constant to understand their role in characterization of induced oxidation. A probable mechanism has been suggested on the basis of induction factor. It is observed that Mn(V) acts as reactive intermediate and induces the oxidation of formic acid through anhydride formation.